2017
DOI: 10.1186/s12955-017-0587-y
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in patients with diabetic foot ulceration — translation and Polish adaptation of Diabetic Foot Ulcer Scale short form

Abstract: ObjectivesDiabetic foot ulcer (DFU) is a common complication of diabetes and not only an important factor of mortality among patients with diabetes but also decreases the quality of life. The short form of Diabetic Foot Ulcer Scale (DFS-SF) provides comprehensive measurement of the impact of diabetic foot ulcers on patients’ health related quality of life (HRQoL). The purpose of this study was to translate DFS-SF into Polish and evaluate its psychometric performance in patients with diabetic foot ulcers.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
44
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 23 publications
12
44
3
9
Order By: Relevance
“…This suggests that low levels of education and income combined with a long duration of T2DM contribute to the eventual development of infected, diabetic foot ulcers and the deterioration of the patient’s quality of life. These results are similar to those reported in other studies [2632]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that low levels of education and income combined with a long duration of T2DM contribute to the eventual development of infected, diabetic foot ulcers and the deterioration of the patient’s quality of life. These results are similar to those reported in other studies [2632]. …”
Section: Discussionsupporting
confidence: 93%
“…This has a great influence in the development of diabetic foot ulcers because the patients do not fully understand both the importance of taking care of the feet and the severity of having T2DM [20–22]. This is consistent with other studies [2326]. In fact, recent studies have shown that people with a higher level of education are more aware of the severity of having T2DM, take better care of their condition, and participate more in programs devoted to the care of the diabetic foot and the prevention of foot ulcers [27,28].…”
Section: Discussionsupporting
confidence: 86%
“…Annual estimates of lower extremity ulceration (LEU) incidence in the general population of the Western world are between 1% and 4.1%, with prevalence ranging from 4% to 10% . The estimated lifetime risk of a person with diabetes mellitus developing a foot ulcer is 15% to 25% .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, his study only investigated three domains of QOL. Other previous studies revealed that the domains of QOL in patients with diabetic foot ulcer consisted of 11 domains including the domains of leisure activities, physical health, daily activities, emotions, noncompliance, family life, friends, foot and wound treatment, satisfaction toward medical care, positive attitude, and financial ability (Macioch et al, 2017;Prazeres & Figueiredo, 2014;Spanos et al, 2017). The assessment of the QOL and its associated factors is important for nurses since a previous study revealed that 85% of amputations were due to complication from diabetic foot ulcer and low QOL (Gilpin & Lagan, 2008).…”
mentioning
confidence: 99%
“…Unfortunately, most studies about the QOL of patients with diabetic foot ulcer were conducted in developed countries (Macioch et al, 2017;Prazeres & Figueiredo, 2014;Spanos et al, 2017). Until now, studies about QOL in patients with foot ulcer conducted in developing countries are very limited, and no studies exist that investigated the associated factors of QOL in patients with diabetic foot ulcer in Indonesia.…”
mentioning
confidence: 99%